Quasi Statistical Convergence of Double Sequences in Neutrosophic Normed Spaces (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we introduce the notion of quasi statistical convergence of double sequences in the neutrosophic normed spaces mainly as ageneralization of statistical convergence of double sequences. We investigate afew fundamental properties of the newly introduced notion and examine therelationship with statistical convergence of double sequences in the neutrosophic normed spaces. In the end, we introduce the concept of quasi statisticalCauchy sequence of double sequences and show that quasi statistical Cauchysequences for double sequences are equivalent to quasi statistical convergentdouble sequences in the neutrosophic normed spaces.